UMPSA community holds first Friday Prayer in new mosque - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 5 July 2024 - The community of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) performed their first Friday prayer in the newly completed and fully operational mosque at UMPSA Pekan.